2019
DOI: 10.1007/s40487-019-0095-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of All-Trans-Retinoic Acid in High-Risk Acute Myeloid Leukemia with Overexpression of EVI1

Abstract: Introduction: EVI1 (MECOM)-positive acute myeloid leukemia (AML) cells have shown in vitro sensitivity to all-trans-retinoic acid (ATRA) by inducing differentiation, cell death, and decreased leukemic engraftment. Methods: In this pilot study, we investigated the response to ATRA in 13 high-risk AML patients with overexpression of EVI1. Results: Seven of the 13 patients (53.8%) achieved complete remission (CR), and response can be combined with a decreased of the leukemia stem cell pool. Conclusion: These prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
(49 reference statements)
0
5
1
Order By: Relevance
“…Transferring this knowledge to the aberrant NRIP1-abstracted upstream control of EVI1 that is unique to t(3;21)(q26;q11) AML would therefore theoretically open a therapeutic window for RA receptor antagonists, which might help to reduce or even abrogate expression of the EVI1 oncogene in these cases. Our data and those from Nguyen et al as well as a recent clinical study do not convincingly show a benefit for adding ATRA to the treatment of EVI1-expressing AML patients 43. As knockdown of NRIP1 negatively affected the proliferation and survival of EVI1-expressing AML cells, our findings warrant further investigation of NRIP1 as a therapeutic target in myeloid diseases with EVI1 activation.ContributionsSG performed experiments, conducted data analyses and wrote the manuscript.…”
contrasting
confidence: 82%
See 1 more Smart Citation
“…Transferring this knowledge to the aberrant NRIP1-abstracted upstream control of EVI1 that is unique to t(3;21)(q26;q11) AML would therefore theoretically open a therapeutic window for RA receptor antagonists, which might help to reduce or even abrogate expression of the EVI1 oncogene in these cases. Our data and those from Nguyen et al as well as a recent clinical study do not convincingly show a benefit for adding ATRA to the treatment of EVI1-expressing AML patients 43. As knockdown of NRIP1 negatively affected the proliferation and survival of EVI1-expressing AML cells, our findings warrant further investigation of NRIP1 as a therapeutic target in myeloid diseases with EVI1 activation.ContributionsSG performed experiments, conducted data analyses and wrote the manuscript.…”
contrasting
confidence: 82%
“…In chromosome 21 intact cells, these elements mediate a strong induction of NRIP1 transcription upon stimulation with ATRA. Treating t(3;21)(q26;q11) cases with ATRA, as suggested in a recent clinical study,43 would therefore coordinate a similarly pronounced upregulation of the EVI1 oncogene in these special cases, presumably with devastating consequences. Another finding of our analyses of NRIP1 regulation is that the absence of RA receptor signaling -as in t(15;17) AML -abrogates NRIP1 expression.…”
mentioning
confidence: 86%
“…Meanwhile, EVI1-positive AML with presumable rearrangements of KMT2A gene was found in one-fourth of pediatric patients [8][9][10], thus also presenting essential age-dependent differences in responses to therapy and HSCT. At the same time, an excellent response to retinoid treatment has been recently revealed in all types of EVI1-positive AML [11], which seems to be associated with their direct action upon functional activity of stem cells [12].…”
Section: Introductionmentioning
confidence: 91%
“…Two studies demonstrated that ATRA could induce differentiation and apoptosis in EVI-1 overexpressing non-APL cell lines and primary samples [ 61 , 62 ]. Despite these encouraging preclinical findings, the role for ATRA or ATO for non-APL AML in a clinical context remains unclear [ 63 , 64 ]. Other selective RARα agonists, such as tamibarotene (SY-1425) have been shown to induce differentiation and apoptosis in high RARα expressing AML primary cells [ 65 ].…”
Section: The Original Differentiation Therapy: All-trans Retinoic Acid and Arsenic In Acute Promyelocytic Leukemiamentioning
confidence: 99%